The impact of health resource enhancement and its spatiotemporal relationship with population health - Qiu, Leijie; Yang, Linsheng; Li, Hairong; Wang, Li (Frontiers in Public Health, 2023)
Objective: This study investigated the impact of health resource enhancement on health and spatiotemporal variation characteristics from 2000 to 2010 at the county level. Methods: Multiscale Geographically Weighted Regression and curve fitting were used to explore the characteristics of spatiotemporal impact and divergence mechanism of health resource enhancement on population health. Results: From 2000 to 2010, China’s population health continued to rise steadily, and health resource allocation improved. Population health demonstrated the significant spatial autocorrelation, and its spatial clustering patterns were relatively fixed. Health resource allocation was relatively equal. Health technicians per 1,000 persons had a significant positive effect on population health in 2000 and 2010. Meanwhile, its impact tends to be consistent across regions, and the impact scale has been continuously expanding. A quantitative relationship exists between population health and health resource inputs. When life expectancy ranged from 73.68 to 84.08 years, the death rate ranged from 6.27‰ to 9.00‰, and the infant mortality rate ranged from 0.00‰ to 6.33‰, investments in health resources, especially related to health technicians, were beneficial for population health. Conclusions: The government should improve the science and rationality of health resource planning. Planning meets regional realities by combining the impacts of economy and geography. The influence of health resources on population health depends on the overall allocation of health technicians. The number of health technicians needs to be further increased to improve the health resources’ effective allocation between regions.